HUBUNGAN pH SALIVA DENGAN KARIES GIGI PADA SISWA KELAS I SD NEGERI 3 GUNTUNG MANGGIS KOTA BANJARBARU - Mukni, Mukni; Habibah, Siti Sab'atul; Nuryati, Sri (JURNAL TERAPIS GIGI DAN MULUT, 2024)
Dental caries is a disease caused by the interaction of acid-producing bacteria with the host (teeth), substrate (food), and develops over time. Acid will cause a repeated decrease in pH over a period of time, then result in tooth demineralization and caries. Basic Health Research 2018 states that South Kalimantan has a caries rate of 56.17% in the age group of 5-9 years. Data on dental caries for elementary school children in the work area of the Guntung Manggis Health Center in 2022 was 64.16%. State Elementary School 3 Guntung Manggis has the highest prevalence rate of dental caries of 92% in the working area of the Guntung Manggis Health Center. The study aimed to determine the correlation between saliva pH and dental caries in grade I students of State Elementary School 3 Guntung Manggis Banjarbaru City. This type of research is an analytical survey with a Cross Sectional research design. The sample was taken by the Proportional Random Sampling technique with a sample of 92 students. The research uses a statistical test, namely Chi Square. The results of this study showed that most students had acidic saliva pH (73.9%) and high dental caries (53.3%). Based on the results of the Chi Square test with a value of sig. (2-tailed) ρ = 0.008 < α = 0.05, which means that Ho is rejected and Ha is accepted. The conclusion is that there is a correlation between saliva pH and dental caries in grade I students of State Elementary School 3 Guntung Manggis Banjarbaru City. It is hoped that it is necessary to improve dental and oral health care service activities, especially promotive and preventive activities, namely continuous counseling and examination at State Elementary School 3 Guntung Manggis, Banjarbaru City to prevent dental caries